INTERNATIONAL LEGAL PROTECTION OF WOMEN'S LABOR RIGHTS. - Begimkhon Abdurakhimova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The issue of women's labor rights realization as a vulnerable demographic has spread throughout the global society. Regardless of whether a state is a party to ILO conventions and recommendations, recognition of a woman as an equal labor unit due to her social and work vulnerability must be established and secured by international labor standards and labor legislation. Government policy should prioritize protecting women's labor rights, and safe and equitable working conditions should take the place of labor limitations. The article investigates the mechanisms of international legal regulation for the protection and promotion of women's labor rights in the areas of maternity protection, women's night work, and the use of women's labor in underground work in accordance with the provisions of ILO conventions and recommendations, as well as the effectiveness of the application of international control mechanisms of the UN Committee on the Elimination of Discrimination Against Women.